The Influence of Price and Promotion on Purchasing Decisions at the Helmi Elektronik Store in Tanjung Raja, Ogan Ilir - Tessa Anggela Putri; Heri Fitriadi; Nidyawati Nidyawati (Universitas Dehasen Bengkulu, 2026)
Against the backdrop of intense competition in local electronics retailing, this study evaluates the extent to which price and promotion influence consumers’ purchase decisions at Helmi Electronics Store, Tanjung Raja (Ogan Ilir). Adopting an associative quantitative approach, we derived a 62-respondent sample using Slovin’s formula and incidental sampling. Data were gathered via questionnaire, subjected to reliability–validity checks and classical assumption testing, and subsequently estimated through multiple linear regression with SPSS v30. Findings are consistent and robust: both price and promotion exhibit positive, statistically significant effects on purchase decisions, and their simultaneous influence remains significant. The coefficient of determination (R²) of 0.875—high for a retail context—suggests that the bulk of variation in purchasing decisions is accounted for by these two variables, with the residual 12.5% attributable to unmodeled factors. While the use of incidental sampling warrants cautious generalization, the evidence provides a strong signal that customers in this setting are highly responsive to competitive pricing policies and targeted promotional activities.